The potential role of cultural and religious healing practices in shaping community vulnerability to highly infectious diseases in western Kenya. - Naomi Wambui Ng'ang'a; Reuben Onkoba Momanyi; Caleb Chemirmir; Hazael Biwott; George Ayodo; Monica Orero; Damaris Ochanda; Sarah Ngere; Winnie Ogola; Titus Murundu; Geoffrey Munene; Zachary Misiani; et al. (PLOS Global Public Health)
Cultural and religious practices and beliefs have historically played a significant role in the management of disease outbreaks globally. This study explored how such beliefs and healing practices shape the vulnerability of communities to highly infectious diseases in three border counties in western Kenya-Homa Bay, Bungoma, and West Pokot. Using an empirical qualitative research design, we conducted 45 key informant interviews with 13 traditional healers, 16 religious healers, and their 16 patients. We also held 6 focus group discussions with community members knowledgeable about cultural customs and practices, and 1 participatory inquiry workshop with health professionals and administrators. The findings indicated that traditional and religious beliefs and healing practices influence community vulnerability to highly infectious diseases in two main ways. Firstly, we identified a dualistic illness etiology that includes both biomedical and socio-cultural interpretations. Traditional and religious healers often served as the first point of care for unexplained illnesses or those unresponsive to conventional medicine, which could delay appropriate treatment and compromise safe handling in case of highly infectious diseases. Second, we found that traditional and spiritual healing practices pose certain risks. Practices such laying of hands, use of herbs and rituals involving slaughtering of animals enhanced contacts. The use of protective gear among healers was inconsistent and often absent due to cost or fears that it could undermine the patient's faith in the healer's powers. These practices can potentially predispose individuals to highly infectious diseases, enhancing transmission and symptom severity. To mitigate the vulnerability of border communities to highly infectious diseases, we recommend comprehensive strategies that address the intersection of vulnerability factors, including healing beliefs and practices. This may involve policy initiatives to integrate traditional medicine practices with the mainstream health system, thereby enhancing disease prevention and control efforts.